"At Home, with Care": Lessons from New York City Home‐based Primary Care Practices Managing COVID‐19. Issue 2 (20th November 2020) - Franzosa, Emily; Gorbenko, Ksenia; Brody, Abraham A.; Leff, Bruce; Ritchie, Christine S.; Kinosian, Bruce; Ornstein, Katherine A.; Federman, Alex D.
Abstract : Background/Objectives: COVID‐19 required rapid innovation throughout the healthcare system. Home‐based primary care (HBPC) practices faced unique challenges maintaining services for medically complex older populations for whom they needed to adapt a traditionally hands‐on, model of care to accommodate restrictions on in‐person contact. Our aim was to determine strategies used by New York City (NYC)‐area HBPC practices to provide patient care during the first wave of the COVID‐19 pandemic with the goal of informing planning and preparation for home‐based practices nationwide. Design: Cross‐sectional qualitative design using semi‐structured interviews. Setting: HBPC practices in the NYC metro area during spring 2020. Participants: HBPC leadership including clinical/medical directors, program managers, nurse practitioners/nursing coordinators, and social workers/social work coordinators (n = 13) at 6 NYC‐area practices. Measurements: Semi‐structured interviews explored HBPC practices' COVID‐19 care delivery challenges, adaptations, and advice for providers. Interviewers probed patient care, end‐of‐life care, telehealth, community‐based services and staffing. Interviews were recorded and transcribed. Data were analyzed through a combined inductive and deductive thematic approach. Results: Participants described care delivery and operational adaptations similar to those universally adopted across healthcare settings during COVID‐19, such as patient outreach and telehealth. HBPC‐specific adaptations included mental health services for patients experiencing depression and isolation, using multiple modalities of patient interactions to balance virtual care with necessary in‐person contact, strategies to maintain patient trust, and supporting team connection of staff through daily huddles and emotional support during the surge of deaths among long‐standing patients. Conclusion: NYC‐area HBPC providers adapted care delivery and operations rapidly during the height of the COVID‐19 pandemic. Keeping older, medically complex patients safe in their homes required considerable flexibility, transparency, teamwork, and partnerships with outside providers. As the pandemic continues to surge around the United States, HBPC providers may apply these lessons and consider resources needed to prepare for future challenges.